THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIALTECHNOLOGY ON FINANCIAL INCLUSION OF ISLAMIC BANKING (Study on FEBI Students of UIN Raden Intan Lampung) - Bella Bevika; Ridwansyah; Bahtiar, M. Yusuf (LP2M IBK Nitro, 2025)
This study aims to analyze the influence of financial literacy and financial technology on financial inclusion in Islamic banking, focusing on students of the Faculty of Islamic Economics and Business (FEBI) UIN Raden Intan Lampung. Financial inclusion is an important aspect in driving economic growth, especially through public access to Islamic banking services that are in accordance with Islamic principles. Islamic financial literacy is increasing as a result of advances in financial technology (fintech), which allows students to better understand the available financial technology services, such as financing, financial arrangements, efforts to encourage the financial system to be accessible to the entire community in driving quality economic growth. This type of research is quantitative research using primary data, to obtain data the researcher used a research instrument in the form of a questionnaire distributed to students of the Faculty of Islamic Economics and Business (FEBI) UIN Raden Intan Lampung. The population of 5000 and a sample of 357 respondents were calculated using the Krejcie and Morgan tables. The sampling technique used the proportional random sampling method. The analysis technique used was multiple linear regression analysis with the help of IBM SPSS software version 25. The results of the study showed that partially financial literacy and financial technology had a significant positive effect on the financial inclusion of Islamic banking in FEBI UIN Raden Intan Lampung students. Simultaneously, both variables had a significant effect on the financial inclusion of Islamic banking in FEBI UIN Raden Intan Lampung students.